2017
DOI: 10.1007/s11230-017-9704-x
|View full text |Cite|
|
Sign up to set email alerts
|

Mayarhynchus karlae n. g., n. sp. (Acanthocephala: Neoechinorhynchidae), a parasite of cichlids (Perciformes: Cichlidae) in southeastern Mexico, with comments on the paraphyly of Neoechynorhynchus Stiles & Hassall, 1905

Abstract: Mayarhynchus n. g. (Acanthocephala: Neoechinorhynchidae) is erected for Mayarhynchus karlae n. g, n. sp. described from the intestine of four species of cichlid fishes distributed from southeastern Mexico. The new genus placed in the family Neoechinorhynchidae (Ward, 1917) Van Cleave, 1928, is readily distinguished from the other 17 genera in the family by having a small proboscis armed with 45-46 relatively weak rooted hooks arranged in nine longitudinal rows of five hooks each. In addition, Mayarhynchus n. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Neoechinorhynchus is the most diverse genus within acanthocephalans, with 117 described species distributed worldwide (Amin, 2013; Smales, 2013; Pinacho-Pinacho et al ., 2014). A few species of the genus Neoechinorhynchus have been analysed using molecular data, suggesting that the genus is paraphyletic (Pinacho-Pinacho et al ., 2017), which is consistent with our phylogenetic trees inferred with three molecular markers. Therefore, the genus Neoechinorhynchus requires a taxonomic revision.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Neoechinorhynchus is the most diverse genus within acanthocephalans, with 117 described species distributed worldwide (Amin, 2013; Smales, 2013; Pinacho-Pinacho et al ., 2014). A few species of the genus Neoechinorhynchus have been analysed using molecular data, suggesting that the genus is paraphyletic (Pinacho-Pinacho et al ., 2017), which is consistent with our phylogenetic trees inferred with three molecular markers. Therefore, the genus Neoechinorhynchus requires a taxonomic revision.…”
Section: Resultssupporting
confidence: 90%
“…Finally, between N. (N) panucensis and N. (N) emyditoides , genetic divergences were 21% for LSU, 35% for ITS and 27% for cox 1. These high levels of genetic divergence among species are similar to those exhibited within Neoechinorhynchus , ranging between 2.3 and 46.8% for LSU, 4.7 and 61.9% for ITS and 9.7 and 59.2% for cox 1 (Pinacho-Pinacho et al ., 2014, 2015, 2017, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the monophyletic and/or paraphyletic assemblage of N. johnii , we found that the sequences were not construed as a monophyletic assemblage in both regions (18S and ITS1-5.8S-ITS2) analyses. The present analyses show that the genus is paraphyletic and our phylogenetic trees corroborate the findings of other researchers [24, 34]. Thus, the genus Neoechinorhynchus requires more investigation as it has rich species diversity and, most likely, does not represent a monophyletic group.…”
Section: Discussionsupporting
confidence: 89%
“…Phylogenetic analysis demonstrated that N. johnii occupies a separate position in the trees, probably indicating an Asian origin of this species. It has already been described in various studies that the genus Neoechinorhynchus harbors rich species diversity [3, 33, 34], but the lack of molecular data from the Asian region for species of Neoechinorhynchus demonstrates that the sampling of members of the genus, especially in Asia, is still incomplete. Previous molecular studies also reported paraphyly within the Palaeacanthocephala [28, 37], while findings related to monophyly in Eoacanthocephala are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%